PENGARUH SENAM LANSIA TERHADAP PENINGKATAN KEBUGARAN FISIK PADA KELOMPOK LANSIA PEREMPUAN DI DESA DAUH PURI KAUH DENPASAR BARAT - Ari Widiastuti; Ari Wibawa; Indah Sri Handari; I Wayan Sutadarma (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACT The increasing number of elderly populations give rise social, economic and health. One of the common health problems is functional impairment of the body that will have an impact on the decline of physical fitness. Research was to determine the effect of the increase in the elderly gymnastics physical fitness in elderly with draft Pre Test - Post Test Control Group Design. Sampling techniques using random sampling with the number of respondents 34 people. The results of the study of physical fitness increase by Paired Sample T-Test in the treatment group p value = 0.000 (p <0.05), while the control group p value = 0.438 (p <0.05). Independent Sample T-Test showed the value of p = 0.000 (p <0.05), which means that there is a significant difference in the value of physical fitness levels both groups. It can be concluded that the exercises of the elderly can improve the physical fitness of the elderly. Keywords: gymnastics elderly, physical fitness.